Reversible sol-to-gel transformation of uracil gelators specific colorimetric and fluorimetric sensor for fluoride ions - Xing, Ling-Bao (Langmuir : the ACS journal of surfaces and colloids, 2013)
A new type of anthracene organogelator based on uracil was obtained using organic aromatic solvents, cyclohexane, DMSO, ethanol, and ethyl acetate. It was further characterized by field-emission scanning electron microscopy and transmission electron microscopy. Specifically, the resulting organogels were demonstrated to be promising colorimetric and fluorescent sensors toward fluoride ions with high sensitivity and selectivity, accompanying the disruption of the gelators. Spectroscopic study and (1)H NMR titration experiment revealed that the deprotonation of the hydrogen atom on the N position of uracil moiety by fluoride ions is responsible for the recognition events, evidenced by immediate transformation from the sol phase to the gel state upon adding a small amount of a proton solvent, methanol. The process is reversible, with zero loss in sensing activity and sol-to-gel transformation ability even after five runs